TINGKAT PENGETAHUAN PASIEN TERHADAP BEYOND USE DATE (BUD) OBAT RACIKAN DI APOTEK KIMIA FARMA 180 PAHLAWAN SIDOARJO - andri priyoherianto; Valiandri Puspadina; Merry Patrilinilla Chresna (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Abstrack Almost people usually spare medicine for supplies. If medicines not stored appropriately, medications can be exposed to varying environmental changes, making them lose their efficacy and it can be harmful to consumer’s health. for example, irrational drug use and cause drugrelated problems, including the risk of medication errors. When a product is opened, assigning a Beyond Use Date (BUD) often requires by the pharmacist to determine appropriate expired date of product. This research is a descriptive observational study. Method of data collection was carried out prospectively during April 2022. This study was conducted to patient’s knowledge level of the Beyond Use Date (BUD) of compounded drugs in Kimia Farma 180 Pahlawan Pharmacy Sidoarjo. From research conducted in April 2022, many recipes were found, both mixtures of powder, capsules, ointments, and syrups. This level of knowledge is obtained based on the results of the answers from the questionnaire sheet with a total of 10 questions to patients who come to redeem prescription medicine. Based on the results of the study, with a total of 171 respondents, it can be concluded that respondents have a level of knowledge that is included in the sufficient category with a value of 53.8%.